Arbeit im Nationalsozialismus - Buggeln, Marc (De Gruyter, 2014)
Work was a core concept in National Socialism. In pre-war concentration camps, it was a tool for converting prisoners into Volksgenossen, or members of the national community. And during the war, forced labor was crucial to armaments production. "Ability to work" meant life or death for Jews, POWs, and others. The essays in this volume explore the multiple meanings of work as a social, political, and cultural practice in National Socialism.